ANALISIS FAKTOR DETERMINAN TERJADINYA KECENDERUNGAN KECURANGAN (STUDI PADA PEMERINTAH PROVINSI PAPUA) - Hesty Theresia Salle; Meinarni Asnawi; Anthonius H. Citra Wijaya (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
The study conducted to examine the effects of compensation suitability, leadership authority, internal control system, information asymmetric, regulatory enforcement and moral reasoning to the fraud tendency—unethical behaviour used as mediating variable. I raised the data using a survey. The data is analyzed using WrapPLS 6.0 application. The result shows that the leading authority and moral reasoning have an effect on the tendency of fraud, while compensation suitability, internal control system, information asymmetry, regulatory enforcement, and unethical behaviour has no effect. Furthermore, unethical behaviour does not mediate the compensation suitability, leadership authority, internal control system, information asymmetry, regulatory enforcement, and moral reasoning.